The environmental agenda in alternative media in Ibero-America: key issues and challenges - Sánchez Torres , Mabel (Multidisciplinar (Montevideo), 2025)
The article reflects on the challenges of the environmental agenda promoted by alternative media born in the digital environment. After a critical review of the scientific literature on the treatment of the subject in Ibero-America, the text aims to shed light on the debate on the concept of alternative journalism, understood as a journalistic practice that prioritizes the depth, veracity and added value of the information as opposed to the mercantilist and liberal sense of traditional media companies. In addition, it delves into the trends of the environmental agenda and the approach to climate change in particular, and points out the main challenges of alternative media to promote a sustainable agenda.